High-dose Chemotherapy With Autologous Stem Cell Rescue in Saudi Children Less Than 3 Years of Age With Embryonal Brain Tumors. Issue 3 (April 2015) - Alsultan, Abdulrahman; Alharbi, Musa; Al-Dandan, Sadeq; Bayoumi, Yasser; Alharbi, Talal; Alsudairy, Reem; Alomari, Ali; Aljamaan, Khalid; Musleh, Othman; Alharbi, Qasim; Jarrar, Mohammed
<x xml:space="preserve">Abstract</x> High-dose chemotherapy with autologous stem cell rescue (HDC/ASCR) has been used in children under the age of 3 years with embryonal brain tumors to avoid or delay the use of radiation. We reviewed the medical records of 10 Saudi children less than 3 years of age with embryonal brain tumors who underwent HDC/ASCR. All 10 patients underwent surgical resection followed by 3 to 5 cycles of induction chemotherapy and 1 to 3 cycles of HDC/ASCR using carboplatin and thiotepa. Isotretinoin was used as a maintenance therapy in 4 patients. Five patients had medulloblastoma, 3 had atypical teratoid/rhabdoid tumors, 1 had an embryonal tumor with abundant neuropil and true rosettes, and 1 had pineoblastoma. The median age of the patients was 1.9 years. A total of 19 HDC/ASCR procedures were performed. Radiotherapy (RT) was administered to 5 patients after HDC/ASCR and as a salvage therapy in 1 patient. The progression-free survival rate was 50% at 1 year and at 2 years, with a median follow-up of 24 months. All 5 patients with medulloblastoma are still alive without evidence of disease, but the other patients died secondary to tumor progression. This experience suggests that strategies combining myeloablative chemotherapy and autologous stem cell rescue appear to be feasible for children with embryonal brain tumors in the Middle East.